Mapping research trends of insulin resistance in polycystic ovary syndrome from 2017 to 2021: A bibliometric analysis - Chen, Yong; Zhang, Qian; Ma, Jinhui; Yu, Yuexin (Frontiers in Endocrinology, 2022)
Introduction To map publication trends and explore research hotspots of insulin resistance (IR) in polycystic ovary syndrome (PCOS) study. Methods With the theme of “Polycystic ovary syndrome” AND “Insulin Resistance”, the key data set of Science Core Literature Collection (WoSCC) web from 2017 to 2021 was extracted and bibliometric analysis was performed. Through VOSviewer v1.6.10 software, the research trend in this field is analyzed visually. Results 2080 literatures about IR in PCOS from 2017 to 2021 were downloaded. The following basic information was collected for each article: country, author, institution, journal, references. The key words are divided into six categories: (1) The interaction between insulin resistance and chronic inflammation; (2) The relationship between insulin resistance and metabolic syndrome and nonalcoholic fatty liver disease; (3) The interaction between insulin resistance and hyperandrogenemia; (4) The relationship between insulin resistance and dyslipidemia; (5) Metformin may regulate insulin resistance in the treatment of PCOS; (6) The study of serum biomarkers in PCOS patients with insulin resistance. Discussion The six key words extracted can provide an in-depth perspective for the study of IR in PCOS, and provide valuable information to help researchers identify potential research directions, collaborators and cooperative institutions.